Effect of age on hepatic lipogenic enzyme activities and fat accumulation in broiler chicks - U Santoso; K Tanaka (Jurnal Ilmu Ternak dan Veteriner, 2001)
The present study was conducted to evaluate effect of age on hepatic lipogenic enzyme activities and lipid fraction in broiler chicks. Eighty broiler chicks were distributed into one group. Broilers were fed commercial diet and provided drinking water ad libitum. At 5, 10, 12, 15, 17,20,22,25,27, and 56 days of age (27, 42, and 56 days of age for serum and carcass collection), 5 chicks were selected based on weights and killed. Experimental results show that the older chicks would have lower specific activity of hepatic acetyl-CoA carboxylase (ACC) and fatty acid synthetase (F AS) activities (P<0,01). Age influenced hepatic triglyceride (P<0.05), serum cholesterol ester and free cholesterol (P<O.OI). The older chicks had higher serum phospholipid and triglyceride (P<0.01). The older chicks had higher carcass fat and abdominal fat (P<0,01), and lower carcass moisture (P<0.05). In conclusion, the older chicks had lower specific activities of hepatic ACC and FAS (lipogenic enzymes) with higher lipid accumulation.   Key words: Age, acetyl-CoA carboxylase, fatty acid synthetase, lipid accumulation, broiler chicks